RISKS IN THE ENERGY SECURITY SYSTEM OF UKRAINE: STATUS AND PROSPECTS OF PROTECTION - LAZARENKO, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the risks in the energy security system. It analyzes data from the International Energy Agency regarding the energy intensity of the global economy. The trends in reducing energy intensity and the factors that could enhance energy productivity, specifically the ways of producing GDP per unit of energy consumed, are identified. The processes of rising energy resource prices are characterized. The dynamics of the average quarterly world oil price and the average quarterly customs value of imported natural gas in Ukraine from 2017 to 2022 are investigated. It is noted that oil prices fluctuated from 2020 to 2022 due to global factors such as the COVID-19 pandemic and geopolitical tensions due to the war in Ukraine.The article analyzes the current state of Ukraine's energy system. In 2022, energy resource prices reached high levels due to geopolitical issues, particularly the Russian invasion of Ukraine, which caused significant disruptions in the energy market. It is noted that in 2020-2022, prices for imported natural gas in Ukraine experienced significant fluctuations, reflecting global volatility in energy markets. In 2020, prices were relatively low due to the economic downturn caused by the COVID-19 pandemic, but they began to recover by the end of the year. This price increase had significant consequences for Ukraine's economy, putting pressure on both residential and industrial consumers, leading to higher energy costs. As a result, the necessity for strategic measures to mitigate these fluctuations has become critical, highlighting the importance of energy efficiency, diversification of supply sources, and the development of domestic energy resources.The results of the macroeconomic analysis underscore the importance of reducing energy consumption for Ukraine's economic growth. To ensure energy security, it is necessary to overcome the country's high energy intensity and low energy efficiency through the implementation of comprehensive measures. The main directions include the modernization of energy infrastructure, increasing investment in renewable energy sources, enhancing energy efficiency in industry and construction, reforming the legislative framework, raising public awareness, attracting international aid, supporting low-income households, and implementing the latest Industry 5.0 and circular economy standards. These measures require close cooperation between the government, business, public, and international partners to achieve energy security and economic development in Ukraine.
Keywords: security; risks; energy security; energy intensity; energy markets